ENVIRONMENTAL COMMUNICATION IN INDONESIAN TELEVISION NEWS COVERAGE - Anna Agustina; Tribuana Tungga Dewi; Nathalia Perdhani Soemantri; Noman Yaser Qureshi; Gede Moenanto (ASPIRATION Journal, 2020)
This article aims to present baseline study result on environmental issues broadcasted on Indonesian television stations in the context of Indonesian media system. Data was collected from one year broadcast of 63 TV from July 2017 to June 2018. The study found that eleven out of sixty three television stations broadcasted 425 programs related to environmental issues. The frequency of programs on environmental issues broadcasted in only 11 TV stationsrevealed that it is only small number of Indonesian TV stations broadcast environmental news. Content analysis method conducted to identify annual distribution of the news within the context of dry and rainy season, news sources, and issues. The study identified that in most of the cases, government officials and the minister or representatives of the Ministry of Environment and Forestry in central and regional governments were quoted as sources. In general, news sources were not representing stakeholders of environmental problems. The contents broadcasted the most were related to forest fire including: forest fires, hotspot, smog, peat and land use change. The environmental issues covered were mostly related to those emerging in dry season in Indonesia, thus ignoring the problems emerged during rainy season. This study has found that Indonesian TV channels have not played significant role in mainstreaming environmental issues and contributing to educating and sensitizing the Indonesian public about environmental issues.